An analysis of the website development practice: a study of e-government website in Malaysia / Mohammad Hafiz Ismail - Ismail, Mohammad Hafiz (2016)
Website development broadly refers to the processes and technology to create a website, with every functionality and content have been prepared on webpage. Development of the Information and Communication Technology (ICT), have stimulated the use of web-based technology rapidly. The web-based technology acts asa channel of information. It makes the web as one of the important channels in Malaysian Electronic Government (E-government) services. E-government can be defined as an initiative of the government to take advantage of information technology(ICT) with more convenient access to improve the quality of services that were previously done manually but now handled electronically. E-government is seen as a necessity rather than an option for a country a wants to be competitive. It is important to ensure that e-government website can function more effectively to provide easy access and to improve the quality of services. This study aims to describe the current web development practices in Malaysia. In addition, the problem occurs in the web development are also identified. The qualitative approach is adapted in this study. The interviews conducted with five respondents who are involved in the website development and they came from the government agencies and Government Linked Companies (GLC). A Value Chain of web development practices is constructed to show the current web development practices in Malaysia. The findings of this study reveals that the current practices of website development and problem occurs in the process.